Kruppel-like Factor 4 Protein Regulates Isoproterenol-induced Cardiac Hypertrophy by Modulating Myocardin Expression and Activity - Yoshida, Tadashi (American Society for Biochemistry and Molecular Biology, 2014)
Kruppel-like factor 4 (KLF4) plays an important role in vascular diseases, including atherosclerosis and vascular injury. Although KLF4 is expressed in the heart in addition to vascular cells, the role of KLF4 in cardiac disease has not been fully determined. The goals of this study were to investigate the role of KLF4 in cardiac hypertrophy and to determine the underlying mechanisms. Cardiomyocyte-specific Klf4 knockout (CM Klf4 KO) mice were generated by the Cre/LoxP technique. Cardiac hypertrophy was induced by chronic infusion of the β-adrenoreceptor agonist isoproterenol (ISO). Results showed that ISO-induced cardiac hypertrophy was enhanced in CM Klf4 KO mice compared with control mice. Accelerated cardiac hypertrophy in CM Klf4 KO mice was accompanied by the augmented cellular enlargement of cardiomyocytes as well as the exaggerated expression of fetal cardiac genes, including atrial natriuretic factor (Nppa). Additionally, induction of myocardin, a transcriptional cofactor regulating fetal cardiac genes, was enhanced in CM Klf4 KO mice. Interestingly, KLF4 regulated Nppa expression by modulating the expression and activity of myocardin, providing a mechanical basis for accelerated cardiac hypertrophy in CM Klf4 KO mice. Moreover, we showed that KLF4 mediated the antihypertrophic effect of trichostatin A, a histone deacetylase inhibitor, because ISO-induced cardiac hypertrophy in CM Klf4 KO mice was attenuated by olmesartan, an angiotensin II type 1 antagonist, but not by trichostatin A. These results provide novel evidence that KLF4 is a regulator of cardiac hypertrophy by modulating the expression and the activity of myocardin.